PENGARUH EKSTRAK DAUN PEPAYA (CARICA PAPAYA, LINN.) TERHADAP PENURUNAN INDEKS GINGIVITIS PADA PEMAKAI ALAT ORTODONTIK CEKAT - Hafid Nur Arzanudin; Arlina Nurhapsari; Aning Susilowati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Background: Gingivitis is one of the serious periodontal infection desease and if there is no precise treatment it will cause the loss of tooth. Patient with fixed orthodontic appliance will be easier to be suffered by the gingivitis because the form of the appliance that attached in such a way. The gingivitis treatment has some alternatives derived from nature and traditional medicines. One of the plants which can be used as traditional medicine is papaya leaf (carica papaya L). Purpose: This study was conducted to determine the effect of papaya leaf extract toward the decline of gingivitis index in patient with fixed orthodontic appliance. Method: The method of this research was quasi-experiment with one group pre-post test design which samples were patient with fixed orthodontic appliance. The gingivitis index was examined in the sample which contains of 30 people at before and after treatment. The index was measured by counting gingival amount score devided by the number of teeth examined. The datawere analyzed by using Friedman examination with the degree of significance 0,05. Result: The result of the study shows that before the treatment 56,7% patient with fixed orthodontic appliance have mild gingivitis. And after the treatment, the number of patient with fixed orthodontic appliance with mild gingivitis increase to 93,3%. The significance score based on the Friedman examination was 0,000 (p<0,05). It means there was a meaningful differences between the group which is given papaya leaf extract at before and after the treatment. Conclusion: It can be concluded that papaya leaf extract is able to decrease the gingivitis index of patient with orthodontic appliance